Malignant pleural mesothelioma: Treatment patterns and outcomes from the Spanish Lung Cancer Group. (September 2020) - Remon, J.; Nadal, E.; Dómine, M.; Ruffinelli, J.; García, Y.; Pardo, J.C.; López, R.; Cilleruelo, A.; García-Campelo, R.; Martín, P.; Juan, O.; González-Larriba, J.L.; et al.
Highlights: Epidemiological report of mesothelioma treatment patterns and outcomes in Spain. Despite multimodal intervention, outcomes remain poor (1-year OS of 53.2 %). Performance status, histology and treatment response were independent factors for survival. Trend toward survival benefit was observed among patients receiving maintenancechemotherapy. Abstract: Background: Malignant mesothelioma is a rare but aggressive tumor arising from the pleura, typically associated with exposure to asbestos. The purpose of this investigation was to describe mesothelioma patient characteristics, treatment patterns, and outcomes in Spain. Material and methods: Patients diagnosed with malignant mesothelioma of the pleura were recorded in an anonymous online database (BEMME, Epidemiologic Spanish Malignant Mesothelioma Database) from June 2008 through May 2013. Patient and tumor characteristics at time of diagnosis, as well as subsequent treatments (surgery, radiation, and chemotherapy), were collected. Among patients treated with chemotherapy, we explored type of chemotherapy regimen and outcomes by treatments. Results: A total of 560 malignant pleural mesothelioma (MPM) patients were recorded. The median age at diagnosis was 68 years, mainly with epithelioid histology (62 %), and any asbestos exposure was noted in 45 % of patients. Nearly two-thirds of patients (71 %) received chemotherapy, mainly platinum-pemetrexed combination, as part of their treatment. Surgery and radiotherapy were given in 36 % and 17 % of patients, respectively. The median overall survival (OS) in the whole cohort was 13.0 months (95 % confidence interval (CI), 11.1–14.8 months) with 1-year OS of 53.2 % (95 % CI, 48.7–57.7 %). In patients receiving first-line chemotherapy (N = 315), the median OS was 13.4 months (95 % CI, 10.8–16.0 months), reaching 20.2 months (95 % CI, 17.2–23.2 months) for those 68 patients receiving maintenance chemotherapy. Results of multivariate analyses showed significant association of ECOG-performance status, histology and treatment response with improved OS in MPM patients treated with palliative chemotherapy. Conclusions: Despite multimodal therapeutic intervention, survival of patients with mesothelioma in Spain remains poor. Although it did not reach significance in the multivariate analysis, a meaningful additional survival benefit was observed among those patients receiving maintenance chemotherapy.